Membedah Konsep Takdir dalam Aqidah Islam: Antara Ketentuan Ilahi dan Kebebasan Manusia - Amanda Sephira Nuraini; Billy Ramadhan; Iin Ulfa Royani; Indra Hadi Kurniawan; Muthia Nur Qur’aini; Salsa Sabila Firmansyah Qinthara; Rika Widawati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This article reviews the concept of destiny in Islamic aqeedah with an emphasis on understanding and in-depth study of it. Beginning with an introduction to the concept of destiny, the article discusses the definition of destiny according to Islamic teachings and explains the concepts of divine decree and human freedom. Aspects of divine provisions such as Al-Qadar and destiny are accompanied by the importance of sincere obedience to destiny. Meanwhile, the aspect of human freedom highlights the wisdom behind the granting of freedom and the role of humans in determining their own destiny through choices and actions. The article also explores the relationship between divine decree and human freedom and how this relationship can be understood in the context of everyday life. The article concludes by emphasizing the importance of applying the concept of destiny in daily life and maintaining a balance between accepting destiny and exercising human freedom responsibly.